Escalating Trends of Type 2 Diabetes in Indonesian Youth: A Public Health Perspective on Obesity and Lifestyle - Said, Suanandar (Medicor : Journal of Health Informatics and Health Policy, 2025)
Introduction & Objective : This study analyzes the alarming rise in youth-onset type 2 diabetes mellitus (T2DM) in Indonesia, focusing on lifestyle factors such as obesity, dietary habits, and physical inactivity, while assessing systemic gaps and policy responses to inform targeted intervention strategies. Methodology Summary : A descriptive epidemiological approach was employed, analyzing national health survey data, registry records, and relevant literature from 2010–2024. Key variables included prevalence rates, age specific incidence, dietary habits, physical activity, and obesity trends. The study also reviewed health system capacity and public policy frameworks. Key Results and Discussion : Results indicate that youth T2DM prevalence has reached 2.3% nationally, with adolescents aged 10–19, especially females, showing the highest increase. Primary contributors include obesity (urban youth obesity at 24%), poor nutrition, and reduced physical activity. Urban children were found to be significantly more affected than rural counterparts. Diagnostic infrastructure and pediatric diabetes care remain limited. Influences such as food advertising and weak regulatory frameworks further exacerbate the problem. International models demonstrate that integrated school, community, and healthcare strategies can mitigate risks. Digital tools and regulatory reforms are underutilized in Indonesia but present opportunities for scalable impact. Conclusion and Implications : To mitigate the projected surge in youth onset T2DM, Indonesia must urgently implement school-based screening, regulate unhealthy food advertising to minors, and improve pediatric diabetes care access particularly in underserved regions.